Truvada approved as HIV PreP: are South African doctors ready? Survey measuring willingness to prescribe and attitudes, knowledge, and practises regarding HIV PrEP amongst South African based doctors - Fleurs, Llewellyn (Department of Public Health and Family Medicine, 2017)
HIV prevention has received renewed attention with the release of results from clinical trials dealing with the efficacy and safety of HIV pre-exposure prophylaxis (PrEP), particularly once daily Truvada, within the last decade. The results seemed to suggest that PrEP is efficacious with high levels of adherence. This culminated in the South African Medicines Control Council (MCC) approving use of Truvada as HIV PrEP in December 2015, coupled with the release of SA HIV Clinicians Society guidelines in February 2016. Several issues were found to be involved in prescribing Truvada as PrEP, including clinical monitoring, adherence counselling, and potential for patient behavioural disinhibition. The objective of this thesis is to discuss the results of an online survey administered to South African doctors, on their opinions on the use of Truvada as PreP. Part A deals with the survey protocol and focuses on (1)ethical issues such as approval by the University of Cape Town Research Ethics Committee, and obtaining consent, (2) method of data collection and (3) procedure of data analysis. Part B is a literature review expanding on the topics described in the Background section, including extent of problem posed by HIV, failure to develop a viable HIV vaccine, need for HIV PrEP, review of previous research on HIV PrEP, and the need for a study on South African doctors' opinions on PrEP. Part C is a manuscript that shows the results of the survey, analysis of the data and a discussion on the possible implications.